Morphological and cytological changes of yeast cells at low temperatures - Паляниця, Любов Ярославівна; Косів, Руслана Богданівна; Березовська, Наталія Іванівна; Паньків, Наталія Олегівна (Eastern-European Journal of Enterprise Technologies, 2012)
Yeast Saccharomyces is widely used in food industry, in particular at fermentation products production. The preservation of yeast taxonomical and technological characteristics is important and may be carried out by different methods, among which cryopreservation is the most prospective. Thus, the target of the research was to study the morphological and cytological changes of yeast cells at low temperatures applying light and electron microscopes according to the standard procedure. The results show that freezing at -17 ºС and -50ºС results in partial modification of the cell’s form, damage of the cell membrane, outlet of cell material, modification of karyosomes and external membranes of yeast ascospores. Some cells remain undamaged and do not undergo essential changes. Yeast spores are more resistant to the cryopreservation in comparison with vegetative cells. The results obtained may be used in food industry and biotechnology when choosing the optimal modes of cryopreservation of industrial cultures of yeast.